Ionic Conductivity and Electrochemical Properties of Alginate–NN4NO3-Based Biopolymer Electrolytes for EDLC Application - Mazuki, Norfatihah binti; Rasali, Nur Muhitul Jalilah; Sahraoui, Bouchta; Samsudin, Ahmad Salihin (Makara Journal of Technology, 2020)
In this work, alginate doped with various contents of ammonium nitrate (NH4NO3) as a solid biopolymer electrolyte (SBE) was prepared via casting by using distilled water as a solvent. Impedance studies on alginate–NH4NO3 SBE films were conducted via impedance spectroscopy. The lowest bulk resistance (Rb) showed that the maximum ionic conductivity of the sample containing 25 wt.% NH4NO3 at ambient temperature (303 K) was 5.56 × 10−5 S cm−1. The temperature dependence of ionic conductivity was evaluated, and results confirmed that electrolytes followed an Arrhenius behavior. The highest conducting sample was fabricated into an electrical double-layer capacitor and characterized in terms of its electrochemical properties through cyclic voltammetry (CV) and galvanostatic charge–discharge (GCD) measurement. CV analysis indicated that specific capacitance decreased as the scan rate increased. Conversely, GCD analysis showed that specific capacitance almost remained unchanged for up to 5000 cycles.